Safety Riding Analysis Using the PDCA Concept for Plumbing Fitting Industry Employees in Tangerang - Sofian Bastuti; Rini Alfatiyah (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2022)
Based on Law No. 1 of 1970 every company must prevent accidents (including traffic accidents on the way to and from work), fires occupational diseases. The problem in this study is the number of traffic accidents by employees of the Plumbing Fitting Company in Tangerang. The purpose of this study is to determine the factors that cause traffic accidents and provide solutions for preventing traffic accidents for company employees. Analysis of the factors causing traffic accidents uses the PDCA concept, where this concept has several stages, namely Plan, Do, Check, and Action. The result of this research is employee traffic accidents decreased from 16 accident cases to 3 accident cases or if calculated on average before repair 1.34 accident cases per month and after repair 0.3 accident cases per month decreased by 77.6%.